Peramalan Jumlah Penduduk Miskin di Kabupaten Tangerang Tahun 2023-2025 - Juwita Ningsih; Nur Azizah Komara Rifai (Bandung Conference Series: Statistics, 2024)
Abstract. The Central Bureau of Statistics (BPS) of Tangerang Regency is a non-ministerial government agency in statistics and data processing. BPS Tangerang Regency conducts several surveys in its data collection efforts, including the National Socio-Economic Survey (SUSENAS), which produces poverty data. Poverty in Indonesia is a complex and multidimensional issue, as the poverty rate in a country influences indicators of success in terms of both development and the economy. Indonesia is classified as a developing country, making poverty a significant issue. Tangerang Regency ranked third in Banten for the most poor residents from 2020 to 2022. The purpose of the research on Forecasting the Number of Poor Residents in Tangerang Regency for 2023-2025 is to provide analysis results that can be utilised and considered by the Tangerang Regency government to address poverty in the area. The data used is the Number of Poor Residents in Tangerang Regency, which is non-stationary and contains a trend element. Therefore, the method used is Double Exponential Smoothing. The forecasting results show that in 2023, there will be 291,285 poor residents; in 2024, there will be 308,165; and in 2025, there will be 325,045, indicating an increase in the number of poor residents over the following three periods. Abstrak. Badan Pusat Statistik (BPS) Kabupaten Tangerang merupakan lembaga pemerintahan non kementrian yang bergerak di bidang statistik dan pengolahan data. Dalam pengumpulan data BPS Kabupaten Tangerang melakukan beberapa survei, salah satunya yaitu Survei Sosial Ekonomi Nasional (SUSENAS) yang menghasilkan data kemiskinan. Kemiskinan di Indonesia merupakan masalah yang kompleks dan multidimensi, karena tingkat kemiskinan di suatu negara akan mempengaruhi indikator keberhasilan baik dari segi pembangunan maupun perekonomian negara tersebut. Negara Indonesia merupakan negara yang tergolong masih berkembang, sehingga kemiskinan menjadi masalah utama. Kabupaten Tangerang berada pada urutan ketiga dengan penduduk miskin paling banyak di Banten pada tahun 2020-2022. Tujuan penelitian Peramalan Jumlah Penduduk Miskin di Kabupaten Tangerang tahun 2023-2025 dengan harapan hasil analisis dapat di manfaatkan dan dapat menjadi pertimbangan oleh pemerintah Kabupaten Tangerang untuk mengatasi kemiskinan di Kabupaten Tangerang. Data yang digunakan yaitu Jumlah Penduduk Miskin di Kabupaten Tangerang yang merupakan data tidak stasioner dan mengandung unsur trend, sehingga metode yang digunakan yaitu Double Exponential Smoothing Hasil peramalan pada tahun 2023 sebanyak 291.285, pada tahun 2024 sebanyak 308.165 dan pada tahun 2025 sebanyak 325.045, artinya Jumlah Penduduk Miskin mengalami kenaikan selama 3 periode ke depan.